2020
DOI: 10.2166/wst.2020.240
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of acid mine drainage using by-product of lysine fermentation

Abstract: Abstract The main point of this research is to assess the applicability of condensed molasses soluble (CMS), which is an organic by-product of lysine fermentation, as an environmentally friendly complexing agent in rhizofiltration of heavy metal contaminated acid mine drainage (AMD). First, the ecotoxicological properties (growth inhibition, seed germination) of CMS were examined with often applied indicator plant species such as duckweed (Lemna minor) and lettuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In addition, it should be taken into account that in acid medium there are also potentially dissolved metallic ions. Studies (Chamorro et al 2018) state that the metallic ions in AMD are largely responsible for its toxicity, and Lattuada et al (2009) reach the same conclusion.The toxicity of raw MIW is corroborated by an analogous study (Nagy et al 2020), that also observed toxic effects in duckweed (Lemna minor) when exposed to AMD.…”
Section: Toxicological Assay For Growth and Inhibition Ratesupporting
confidence: 59%
“…In addition, it should be taken into account that in acid medium there are also potentially dissolved metallic ions. Studies (Chamorro et al 2018) state that the metallic ions in AMD are largely responsible for its toxicity, and Lattuada et al (2009) reach the same conclusion.The toxicity of raw MIW is corroborated by an analogous study (Nagy et al 2020), that also observed toxic effects in duckweed (Lemna minor) when exposed to AMD.…”
Section: Toxicological Assay For Growth and Inhibition Ratesupporting
confidence: 59%
“…As AMD is highly acidic and contains a large number of heavy metals, sulfates, and other pollutants [3,4], when it is discharged to the ground, it will cause great pollution to the surrounding water bodies and soil, lower the pH value of surface water, inhibit the growth and reproduction of aquatic organisms, destroy the granular structure of the soil, make the soil caked, salinized, barren, which will lead to the withering and death of crops [5]. In addition, the contaminants in AMD can pose a risk to human health through the food chain [6,7]. Previous studies have shown that AMD has become a long-term source of pollution, as it can continue to be generated for hundreds of years even after mining activities have ceased [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It has to be underlined, that the study of Bech et al [47] concerned soils with basic pH, so despite the geographical proximity, the same plant species presented different behavior. In fact, the use of inorganic and organic amendments to acidic soil is recommended to improve metal removal efficiency by phytoremediation [66,67].…”
Section: Bioconcentration (Bcf) and Translocation Factor (Tf) Of The mentioning
confidence: 99%